Study of Education Policy and Structure of Physically Challenged People in India (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The education of physically challenged individuals in India has been an area of concern and development over the years. Despite various policies and initiatives by the government and non-governmental organizations, numerous challenges persist. This paper aims to explore the current state of education for physically challenged people in India, identify the challenges they face, and highlight successful interventions and future directions for policy and practice. Through an extensive review of existing literature, government reports, and case studies, this paper provides a comprehensive overview of the efforts and obstacles in providing inclusive education to physically challenged individuals in India.